2022
DOI: 10.1101/2022.02.09.479777
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Linear DNA amplicons as a novel cancer vaccine strategy

Abstract: DNA-based vaccines represent a simple, safe and promising strategy for harnessing the immune system to fight infectious diseases as well as various forms of cancer and thus are considered an important tool in the cancer immunotherapy toolbox. Nonetheless, the manufacture of plasmid DNA vaccines has several drawbacks, including long lead times and the need to remove impurities from bacterial cultures. Here we report the development of polymerase chain reaction (PCR)-produced amplicon expression vectors as DNA v… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…Indeed, EP technology is prone to a certain level of variability, as we have observed in murine cancer models [5]. Moreover, it is worth mentioning the indirect evidence observed with linear DNA produced by PCR, which is as immunogenic and efficacious as supercoiled plasmid DNA [12]. In this recent paper, we compared side-by-side PCR-produced linear DNA and plasmid DNA in gene expression and a cancer vaccine model, and showed that the two forms of DNA vaccine delivered by EP resulted in similar immune responses and antitumor effects.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, EP technology is prone to a certain level of variability, as we have observed in murine cancer models [5]. Moreover, it is worth mentioning the indirect evidence observed with linear DNA produced by PCR, which is as immunogenic and efficacious as supercoiled plasmid DNA [12]. In this recent paper, we compared side-by-side PCR-produced linear DNA and plasmid DNA in gene expression and a cancer vaccine model, and showed that the two forms of DNA vaccine delivered by EP resulted in similar immune responses and antitumor effects.…”
Section: Discussionmentioning
confidence: 99%